1992
DOI: 10.1063/1.108030
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of 1.064 μm absorption in Cr,Ca:Y3Al5O12 crystals

Abstract: Saturation absorption experiments are conducted on the title compound at 1.064 μm with laser light propagating along both the [001] and [111] crystallographic axes. Rotation of the crystals about these axes during the experiments reveals that the transmission of the polarized 1.064 μm radiation is highly anisotropic in the saturation regime. The details of the anisotropy and saturation curves are explained using a simple model of subsets of optical centers along with a relevant set of rate equations. The groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(48 citation statements)
references
References 4 publications
2
43
0
3
Order By: Relevance
“…To fully understand the nature of polarization states in passively Q-switched Yb:YAG/Cr,Ca:YAG microchip lasers, we measured the polarization states of Yb:YAG crystals and ceramics by removing Cr,Ca:YAG saturable absorber and found that Yb:YAG crystals oscillate at linearly polarization states selected by the crystalline-orientations in the (111) plane (Dong et al, 2008) and Yb:YAG ceramic oscillates at unpolarization states. Although there is saturation absorption in Cr,Ca:YAG ceramic, the same as that for Cr,Ca:YAG crystal, owing to the random distribution of Cr,Ca:YAG particles in ceramic, the saturation absorption does not exhibit crystalline-orientation dependent anisotropic properties when the sample is rotated, which is different from the anisotropic saturation absorption of Cr,Ca:YAG crystal when the laser propagate along [111] direction (Eilers et al, 1992). Therefore, the polarization states in passively Q-switched microchip lasers with Cr,Ca:YAG as saturable absorber are not only determined by the anisotropic saturation absorption of Cr,Ca:YAG saturable absorber, but also determined by the linearly polarized states of Yb:YAG crystals.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 3 more Smart Citations
“…To fully understand the nature of polarization states in passively Q-switched Yb:YAG/Cr,Ca:YAG microchip lasers, we measured the polarization states of Yb:YAG crystals and ceramics by removing Cr,Ca:YAG saturable absorber and found that Yb:YAG crystals oscillate at linearly polarization states selected by the crystalline-orientations in the (111) plane (Dong et al, 2008) and Yb:YAG ceramic oscillates at unpolarization states. Although there is saturation absorption in Cr,Ca:YAG ceramic, the same as that for Cr,Ca:YAG crystal, owing to the random distribution of Cr,Ca:YAG particles in ceramic, the saturation absorption does not exhibit crystalline-orientation dependent anisotropic properties when the sample is rotated, which is different from the anisotropic saturation absorption of Cr,Ca:YAG crystal when the laser propagate along [111] direction (Eilers et al, 1992). Therefore, the polarization states in passively Q-switched microchip lasers with Cr,Ca:YAG as saturable absorber are not only determined by the anisotropic saturation absorption of Cr,Ca:YAG saturable absorber, but also determined by the linearly polarized states of Yb:YAG crystals.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Average output power increases linearly with absorbed pump power for the four combinations, the slope efficiencies with respect to the absorbed pump power were estimated to be about 39, 36, 36 and 29% for the four combinations of C1, C2, C3 and C4, respectively. The best laser performance (low threshold and high slope efficiency) of passively Q-switched Yb:YAG/Cr,Ca:YAG microchip lasers was obtained with C1 combination because of the enhancement of linearly polarized laser operation due to the combination of linearly oscillation of Cr:YAG crystal under high intracavity laser intensity (Eilers et al, 1992) and the crystalline-orientation selected linearly polarized states of Yb:YAG crystal (Dong et al, 2008). Maximum average output power of 310 mw was obtained with Yb:YAG/Cr,Ca:YAG allcrystal combination when the absorbed pump power was 1.34 W, corresponding to opticalto-optical efficiency of 23%.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17][18][19] >ÿ vÊ* .&~ ÂKßWf êṼ ²w" z>Ú~ zßWö ~. V¢B, > ÿ vÊ* .& ÂK~ 'z¢ * .& îß W" z®Ú z>Ú~ V&çf Vç~ >ßW ö & & Ö 7º~.…”
unclassified